2022
DOI: 10.32800/abc.2023.46.0071
|View full text |Cite
|
Sign up to set email alerts
|

Long distance dispersal of monk parakeets

Abstract: Invasive species threaten biodiversity all around the world and for this reason, identifying the causes and mitigating their effects is a priority in conservation biology. One of the most important factors when dealing with invasive species is dispersal, because the distribution of dispersal distances among members of a population can greatly affect the rate of spread of these invasive populations. Long distance dispersal events have a disproportionately large influence on dispersal kernel estimations, but bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, unlike the results from ( Smith-Vidaurre et al 2020 ), which suggest that selection for individually distinctive calls outweighs any selection for call convergence at the group level, we found very clear evidence for dialects between cities. A possible explanation for this discrepancy is that the study undertaken by Smith-Vidaurre et al (2020) was undertaken in the native distribution of monk parakeets, while our results were obtained in a large invasive range where populations are fragmented and dispersal between populations (i.e., cities) is very unlikely ( Borray-Escalante et al 2023 ; Bucher et al 1990 ; Dawson Pell et al 2021 ). In contrast, although dispersal patterns have not been fully described in the native range, the habitat is more continuous, with increases in Eucalyptus trees allowing for long distance dispersal across the entire range ( Da Silva et al 2010 ; Bucher and Aramburú 2014 ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, unlike the results from ( Smith-Vidaurre et al 2020 ), which suggest that selection for individually distinctive calls outweighs any selection for call convergence at the group level, we found very clear evidence for dialects between cities. A possible explanation for this discrepancy is that the study undertaken by Smith-Vidaurre et al (2020) was undertaken in the native distribution of monk parakeets, while our results were obtained in a large invasive range where populations are fragmented and dispersal between populations (i.e., cities) is very unlikely ( Borray-Escalante et al 2023 ; Bucher et al 1990 ; Dawson Pell et al 2021 ). In contrast, although dispersal patterns have not been fully described in the native range, the habitat is more continuous, with increases in Eucalyptus trees allowing for long distance dispersal across the entire range ( Da Silva et al 2010 ; Bucher and Aramburú 2014 ).…”
Section: Discussionmentioning
confidence: 74%
“…The term colony is often defined as one or more nest structures located within 200 m of each other (see Reed et al (2014) , Supplementary Materials ). In cities and invasive populations, these nesting colonies are often located within parks or other green areas, clearly delineated from other colonies, although with potential between-park movement and dispersal ( Borray-Escalante et al 2023 ; Bucher et al 1990 ). A recent study in the native range of monk parakeets found evidence that individual signatures outweighed any emergent dialects ( Smith-Vidaurre et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by taking into account that the monk parakeet has invaded Mexico for some years (CONABIO, 2015) and that the colonization process is probably not over. Although the speed of dispersion of this species is low and there is no evidence that it conducts long-distance movements (10 km, Borray-Escalante et al, 2023), it is likely that the settlement of the sites estimated as favorable by the model is slow. Especially considering that these sites have continuity with those that have presence recorded and with favorable or intermediate favorable characteristics (0.6).…”
Section: Discussionmentioning
confidence: 99%
“…In these sites, the populations could be well established and act as sources from which monk parakeets disperse toward nearby favorable areas. However, the dispersion of the species observed during recent years has been fast and extensive (Da Silva et al, 2010;Dawson et al, 2021;Borray-Escalante et al, 2023). This phenomenon has been attributed to this species being a broadly traded parrot, whose success in colonization and establishment increases notably with the rate of escape (Duncan et al, 2003), which is why the model generated could be modified by including this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to access mutual foraging patches, birds would need to cross sites separated by urban-suburban areas and highways which may be difficult. Genetic evidence suggests that long-distance dispersal ranging from 10 -100 km is possible in monk parakeets (Borray et al, 2023;Gonçalves da Silva et al, 2010).…”
Section: Strangers Readily Formed Flocks But Stayed Close To Familiar...mentioning
confidence: 99%